Filipino Nursing Students' eHealth Literacy and Criteria Used for Selection of Health Websites - Ryan Michael F. Oducado; Rome B. Moralista (Annals of Tropical Medicine and Public Health, 2020)
Possessing eHealth literacy skills among students has been increasingly appreciated in nursing education. Despite eHealth literacy has been widely studied, little published research is available regarding Filipino nursing students' eHealth literacy. This study aimed to determine the self-reported eHealth literacy of Filipino nursing students and the relative importance of the criteria they use when selecting health websites. A cross-sectional research design was used involving 66 conveniently chosen nursing students. Self-reported data were collected using adopted questionnaires. Data were analyzed using descriptive statistics, the Mann-Whitney U test, and Spearman's rho. Findings revealed that nursing students had high eHealth literacy. The utility of information and accuracy of information were the top criteria students consider important when selecting health websites. There were no significant differences in the eHealth literacy of male and female and first-year and second-year nursing students. The extent of Internet use for health information, perceived usefulness of the Internet when making health decisions, and perceived importance to access health resources on the Internet were significantly correlated with eHealth literacy. To derive full benefit from online health information, nursing students' literacy needs in the Web context and digital environment must be given attention.
Keywords: 330; ehealth literacy; electronic health literacy; internet; nursing; students; Philippines